Translating contemporary scientists’ knowledge and practice into classrooms: Scalable design supporting identity work - Vamvakas, Mary; Tytler, Russell; White, Peta J. (Frontiers in Education, 2023)
There are new demands on science education for students moving into uncertain futures, including engagement with scientific practices, and understanding of the nature of science and scientists’ work. Furthermore, there is increasing recognition of and interest in the construct of identity as a powerful way of looking at students’ engagement with science studies and futures. In Australia there has been policy-level curriculum advocacy focused on finding practical ways to represent scientists, their research practices and specialist knowledge as a powerful context for learning. Research into partnerships shows this has strong identity outcomes and pedagogies that privilege student active engagement with scientific practices. As part of an ongoing research program investigating the possibilities for a more thorough and scalable representation of contemporary science research practices in classrooms, this paper reports on a) a survey of science teachers probing their beliefs and practices regarding representation of contemporary science, and b) the identity entailments of producing and evaluating online resources that represent scientists working in key contemporary areas. The survey identifies that teachers are overwhelmingly positive about representing contemporary science and the varied ways they do that, but also identifies a range of structural barriers resulting in low levels of this practice. We describe the design principles process by which scientists’ practices are translated into classroom learning sequences that engage students with scientists’ backgrounds and motivations, research design and data analysis, and ethical and wider framings of scientific research. Preliminary trialing of the resources (previously reported) shows enhanced student engagement with contemporary, societally relevant scientific knowledge and practices. In this paper we interpret these experiences as identity forming and agency-developing. We argue in the paper that the construction and availability of such resources is a potentially powerful way of engaging students with: the practices of contemporary science; the motivations and living reality of scientists; and the societal and personal relevance of science to students’ lives. Engagement with such resources that involve students in actively generating and responding to contemporary concerns we argue is a more powerful way of introducing science ideas and providing identity-shaping opportunities than current established practices identified in the survey.